Contractualism and the foundations of morality - Southwood, Nicholas (Oxford : Oxford University Press, 2010)
Southwood assesses contractualism as an account of the foundations or ultimate grounds of morality. While sceptical about how contractualism has typically been developed, he proposes a novel 'deliberative' version of contractualism, which he argues has the resources to offer an account of morality's foundations.
Includes bibliographical references.
Description based on online resource; title from home page (viewed Dec. 17, 2010).
Keywords: Contractarianism (Ethics)